2018
DOI: 10.1021/acs.orglett.8b01233
|View full text |Cite
|
Sign up to set email alerts
|

Decarbonylative Methylation of Aromatic Esters by a Nickel Catalyst

Abstract: A Ni-catalyzed decarbonylative methylation of aromatic esters was achieved using methylaluminums as methylating agents. Dimethylaluminum chlorides uniquely worked as the methyl source. Because of the Lewis acidity of aluminum reagents, less reactive alkyl esters could also undergo the present methylation. By controlling the Lewis acidity of aluminum reagents, a chemoselective decarbonylative cross-coupling between alkyl esters and phenyl esters was successful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 48 publications
0
39
0
Order By: Relevance
“…[13] In this context, our interest focused on the use of the organoaluminum reagent itself as a coupling partner of chlorosilanes. [14,15] Herein, we report the nickel-catalyzed crosscoupling reaction of chlorosilanes with organoaluminum reagents for the selective introduction of alkyl substituents into chlorosilanes (Scheme 1d).…”
Section: Nickel-catalyzed Selective Cross-coupling Of Chlorosilanes Wmentioning
confidence: 99%
“…[13] In this context, our interest focused on the use of the organoaluminum reagent itself as a coupling partner of chlorosilanes. [14,15] Herein, we report the nickel-catalyzed crosscoupling reaction of chlorosilanes with organoaluminum reagents for the selective introduction of alkyl substituents into chlorosilanes (Scheme 1d).…”
Section: Nickel-catalyzed Selective Cross-coupling Of Chlorosilanes Wmentioning
confidence: 99%
“…[5] Fori nstance,o ur lab and others recently showed that phenyl esters can be used to make amides (Scheme 1), ketones,biaryls,and more with Pd and Ni catalysis. [7] Towards methyl ester activation, Garg et al recently demonstrated the use of aN i catalyst with stoichiometric Al(Ot-Bu) 3 to enable direct amide bond formation, [8] though the substrate scope was limited to methyl 1-naphthoate esters and N-alkyl aniline derivatives.These transformations were noted to be energetically unfavorable,a nd the aluminum additive was noted to both facilitate CÀOb ond activation and make the reaction more thermodynamically feasible.H ue tal. Thed evelopment of coupling reactions with unactivated esters is needed to make this strategy of general utility.…”
mentioning
confidence: 99%
“…Thed evelopment of coupling reactions with unactivated esters is needed to make this strategy of general utility. [7] Towards methyl ester activation, Garg et al recently demonstrated the use of aN i catalyst with stoichiometric Al(Ot-Bu) 3 to enable direct amide bond formation, [8] though the substrate scope was limited to methyl 1-naphthoate esters and N-alkyl aniline derivatives.These transformations were noted to be energetically unfavorable,a nd the aluminum additive was noted to both facilitate CÀOb ond activation and make the reaction more thermodynamically feasible.H ue tal. accomplished as imilar transformation with more diverse ester starting materials but required in situ generated azobenzene nucleophiles by reduction of aniline derivatives with stoichiometric Zn.…”
mentioning
confidence: 99%
“…Theu se of abundant methyl esters is ap articularly appealing alternative to more activated surrogates.However, the absence of coordinating and/or electron-withdrawing functionality renders oxidative addition into the strong C(acyl)ÀOb ond as ignificant challenge.G arg,H ouk, and co-workers first demonstrated that methyl esters could be activated for cross-coupling reactivity [7] with the use of aN i catalyst. [8] While this transformation was limited to methyl naphthoate derivatives activated by stoichiometric Al-(OtBu) 3 ,l ater reports by the groups of Rueping, [9] Yamagu-chi, [10] and ourselves [11] demonstrated that these limitations could be overcome,albeit at temperatures from 140 to 170 8 8C (Scheme 1B). DFT studies support the hypothesis that aN i 0 catalysts is capable of oxidatively adding to the strong C(acyl) À Obond of amethyl ester with reasonable activation energies, [8,12] though formation of the corresponding acyl-Ni complex is thermodynamically uphill and likely reversible.…”
mentioning
confidence: 99%
“…[18] This side product formation was suppressed in ethereal solvents (entries 8and 9). CsF was found to give comparable yield to K 3 PO 4 (entry 11), while KF was ineffective (entry 10). Surprisingly,amixture of these two was ultimately found to be reproducibly superior to either component alone,i ncreasing the yield of 3a to 72 % (entry 12).…”
mentioning
confidence: 99%